Single Motherhood, Employment, or Social Assistance: Why are U.S. Women Poorer than Women in Other Affluent Nations? - Karen Christopher (Luxembourg Income Study (LIS), 2001)
U.S. women have higher poverty rates than women in other affluent nations. In this paper I attempt to explain this disparity by examining the effect of single motherhood, employment, and social assistance on women's poverty. With cross-national comparisons of quantitative data, I find that the relatively high rate of single motherhood among U.S. women is not a main cause of their high poverty rates. Compared to their counterparts in other Western nations, U.S. women, mothers and single mothers are among the most likely to earn poverty wages. In addition, U.S. social assistance programs are the least effective in reducing poverty. I conclude with the policy implications of my findings, focusing on strategies to ameliorate the high poverty rates of U.S. women and mothers.
Keywords: 330; Alleinerziehende; Armut; Frauen; Öffentliche Sozialleistungen; USA